2012
DOI: 10.1038/nsmb.2467
|View full text |Cite
|
Sign up to set email alerts
|

A pseudoatomic model of the COPII cage obtained from cryo-electron microscopy and mass spectrometry

Abstract: COPII vesicles transport proteins from the ER to the Golgi apparatus. Previous cryoEM structures of the COPII cage lacked the resolution necessary to determine the residues of Sec13 and Sec31 that mediate assembly and flexibility of the COPII cage. Here we present a 12Å-resolution structure of the COPII cage, where the tertiary structure of Sec13 and Sec31 is clearly identifiable. We employ this structure and a homology model of the Sec13-Sec31 complex to create a reliable pseudo-atomic model of the COPII cage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 42 publications
(58 reference statements)
3
66
2
Order By: Relevance
“…This same study also revealed that the Sec23/24 cargo adaptor assembled into a regular lattice on the membrane surface [48] . Taken together, the findings from this and earlier work [43, 44, 49, 46, 47] indicate that the COPII coat can adopt a variety of geometries to accommodate a range of vesicle sizes, with the Sec23/24 adaptor itself playing an unexpected structural role in determining vesicle shape [48] .…”
Section: Copii Coat Assembly May Accommodate Different Cargo Sizessupporting
confidence: 59%
See 1 more Smart Citation
“…This same study also revealed that the Sec23/24 cargo adaptor assembled into a regular lattice on the membrane surface [48] . Taken together, the findings from this and earlier work [43, 44, 49, 46, 47] indicate that the COPII coat can adopt a variety of geometries to accommodate a range of vesicle sizes, with the Sec23/24 adaptor itself playing an unexpected structural role in determining vesicle shape [48] .…”
Section: Copii Coat Assembly May Accommodate Different Cargo Sizessupporting
confidence: 59%
“…Although the polyhedral cage-like structure of the Sec13/31 scaffold surrounding vesicles is well characterized [4247] , a recent cryo-EM structure of complete COPII complexes assembled on membrane tubules uncovered an alternative cylindrical architecture adopted by this scaffold [48] . This same study also revealed that the Sec23/24 cargo adaptor assembled into a regular lattice on the membrane surface [48] .…”
Section: Copii Coat Assembly May Accommodate Different Cargo Sizesmentioning
confidence: 99%
“…Structural studies have established that the adaptability of the COPII coat (i.e., the capacity to adopt vesicular and tubular forms) depends on two molecular features: variable angles at the vertex, and centrally along the edge, of the Sec13/31 cage; and a flexible (unstructured) polypeptide connection between the inner and outer coat proteins (17,22,25). The variable angles enable the Sec13/31 assembly unit to adapt to cages of different curvature (in two dimensions), and the flexible link between Sec23/24•Sar1 and Sec13/31 allows for variation in the geometric relationship between the inner and outer coat proteins (17).…”
Section: Discussionmentioning
confidence: 99%
“…At the later stages of assembly, the outer COPII coat component, the Sec13/31 complex, is recruited. Sec13/31 mediates COPII coat flexibility and plays a structural role in promoting the formation of coats of different geometries [911]. Finally, newly formed COPII-coated vesicles get pinched off from the ER and are shipped along with the encapsulated cargo to their target destinations [4,5].…”
Section: Introductionmentioning
confidence: 99%